Acceptance analysis of PPIUCD in tertiary care centre of north Delhi region - Sweta,; Anjum, Shazia; Mendiratta, Suman Lata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: IUCD is a temporary method of contraception in use for many years in India. Our main objective is to find the acceptance of (postplacental intrauterine contraceptive device) PPIUCD in recent years in the North Delhi region. Methods: An interventional study was carried among the pregnant mothers visiting antenatal outdoor patient department Hindu Rao Hospital and NDMC Medical College during their 28 to 36 weeks of pregnancy over period of 12 months starting from March 2020 to February 2021. Results: The acceptance of PPIUCD was high in the present study where most of the women with higher parity (57%) accepted it and acceptance rate increased from 14% to 48% after counselling the patients and her family. Conclusions: Level of awareness for PPIUCD was poor among women of North Delhi region. PPIUCD can play a pivot role in country’s family planning programme.